PELAKSANAAN EVALUASI PROGRAM BIMBINGAN DAN KONSELING GURU BIMBINGAN & KONSELING SMP DI LAMPUNG - Anugrah Ade Putra; Farah Wahyuni; Lia Amalia Putri; Kristina Berty Artati; Aip Badrudjaman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the gap between the evaluation performance of the Guidance and Counseling (BK) teacher counseling program at the junior high school level in Lampung with predetermined standards. This research uses the type of field research where the research is carried out by going directly to the field to get the actual data. The research design is qualitative in nature where the aim is to describe facts or phenomena between elements of systematic and objective events. The population of junior high school counseling teachers in Lampung. Based on the analysis of the results of the evaluation of the counseling program for junior high school counseling teachers in Lampung, it still needs to be improved. The results of this study recommend counselors to improve the quality of the implementation of the counseling program, so that it can have a positive influence on students.